Development of Hybrid Photovoltaic-Wind System for LED Street Lighting - Mohd Nasir, Mohamad Na'im; Jali, Mohd Hafiz; Rashid, Muhammad Alif Ridzuan; Sulaima, Mohamad Fani; Yahaya, M. S (2013)

(untitled)
This paper presents the development of hybrid Photovoltaic (PV)-Wind system connected to light emitting diode (LED) street lighting as the load. The aim of this research is to analyze the energy performance from the combination of PV system and wind system which is hybrid system to the LED lamp as the load. In this project, the PV panel and wind turbine used to generate the energy and the output of the energy control by two equipments which are solar charger controller and hybrid charger controller. The output of both PV and wind connected with the battery as storage energy for this system. In this research, the PV system produces the best energy compared to the wind system and it is reliable to charge the battery of the system and supply to the load.